2017
DOI: 10.1590/1678-4685-gmb-2016-0249
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies a novel mutation of the GDI1 gene in a Chinese non-syndromic X-linked intellectual disability family

Abstract: X-linked intellectual disability (XLID) has been associated with various genes. Diagnosis of XLID, especially for non-syndromic ones (NS-XLID), is often hampered by the heterogeneity of this disease. Here we report the case of a Chinese family in which three males suffer from intellectual disability (ID). The three patients shared the same phenotype: no typical clinical manifestation other than IQ score ≤ 70. For a genetic diagnosis for this family we carried out whole exome sequencing on the proband, and vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For this variant, we obtained a fitness score of 0.74 +/- 0.03. Individuals in a family carrying the Gly237Val variant had moderate ID 33 , and we observed a corresponding lower fitness score of 0.55 +/- 0.07 for Gly237Val. Thus, the order of the fitness scores for these two variants agreed with the reported order of ID severity.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…For this variant, we obtained a fitness score of 0.74 +/- 0.03. Individuals in a family carrying the Gly237Val variant had moderate ID 33 , and we observed a corresponding lower fitness score of 0.55 +/- 0.07 for Gly237Val. Thus, the order of the fitness scores for these two variants agreed with the reported order of ID severity.…”
Section: Resultsmentioning
confidence: 61%
“…The set of presumed damaging variants consists of the two missense variants with “pathogenic” clinical significance on ClinVar, Leu92Pro 11 and Arg423Pro 15 , as well as a third variant described more recently, Gly237Val 33 . Additionally, four variants were included which were shown to inhibit GDI1 function in functional assays, Tyr39Val, Glu233Ser, Met250Tyr, and Thr248Pro 27 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rab GDI reduces the expression of Rab3A, an active protein related to synaptic vesicles, in the brain tissues of schizophrenic patients [ 32 ]. Previous studies have shown that GDI1 is associated with intellectual disability [ 33 ], hyperexcitability [ 34 , 35 ] and memory formation in the forebrain region of mice [ 36 ]. However, the role of GDI1 in tumors has not been reported.…”
Section: Introductionmentioning
confidence: 99%